New strategies for America's watersheds - National Research Council (U.S.). Committee on Watershed Management (Washington, D.C. : National Academy Press, 1999)
Emergence of a toxic organism like pfisteria in tributaries of the Chesapeake Bay has focused public attention on potential hazards in our water. More importantly, it has reminded us of the importance of the entire watershed to the health of any body of water and how political boundaries complicate watershed management. New Strategies for America's Watersheds provides a timely and comprehensive look at the rise of "watershed thinking" among scientists and policymakers and recommends ways to steer the nation toward improved watershed management. The volume defines important terms, identifies fundamental issues, and explores reasons why now is the time to bring watersheds to the forefront of ecosystem management. In a discussion of scale and scope, the committee examines how to expand the watershed from a topographic unit to a framework for integrating natural, social, and economic perspectives as they share the same geographic space. The volume discusses: Regional variations in climate, topography, demographics, institutions, land use, culture, and law; Roles and interaction of federal state, and local agencies; Availability or lack of pertinent data; and, Options for financing. The committee identifies critical points in watershed planning to ensure appropriate stakeholder involvement and integration of science, policy, and environmental ethics.
Why watersheds? -- Spatial and temporal scales for watersheds -- Regional variations -- Data and information -- Connecting science and the decisionmaker -- Organizing for watershed management -- Financing watershed organizations -- Planning and decisionmaking -- Conclusions and recommendations.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Watershed management -- United States; Bassins hydrographiques -- Gestion -- États-Unis.; NATURE -- Natural Resources; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; Watershed management; United States